7α-Hydroxycholesterol Elicits TLR6-Mediated Expression of IL-23 in Monocytic Cells - Seo, Hyun Chul (Biomol Ther (Seoul), 2015)
We investigated the question of whether 7-oxygenated cholesterol derivatives could affect inflammatory and/or immune responses in atherosclerosis by examining their effects on expression of IL-23 in monocytic cells. 7α-Hydroxycholesterol (7αOHChol) induced transcription of the TLR6 gene and elevated the level of cell surface TLR6 protein in THP-1 monocytic cells. Addition of an agonist of TLR6, FSL-1, to TLR6-expressing cells by treatment with 7αOHChol resulted in enhanced production of IL-23 and transcription of genes encoding the IL-23 subunit α (p19) and the IL-12 subunit β (p40). However, treatment with 7-ketocholesterol (7K) and 7β-hydroxycholesterol (7βOHChol) did not affect TLR6 expression, and addition of FSL-1 to cells treated with either 7K or 7βOHChol did not influence transcription of the genes. Pharmacological inhibition of ERK, Akt, or PI3K resulted in attenuated transcription of TLR6 induced by 7αOHChol as well as secretion of IL-23 enhanced by 7αOHChol plus FSL-1. Inhibition of p38 MAPK or JNK resulted in attenuated secretion of IL-23. These results indicate that a certain type of 7-oxygenated cholesterol like 7αOHChol can elicit TLR6-mediated expression of IL-23 by monocytic cells via PI3K/Akt and MAPKs pathways.